Method and device for predicting fusion degree of new asphalt and old asphalt in hot mix plant recycled asphalt mixture

Test the nanoscale modulus and process parameters of new and old asphalt through atomic force microscope, establish a fitted model to predict the degree of fusion of new and old asphalt, solve the problems of measurement complexity and error in the existing technology, and achieve rapid and accurate prediction of fusion degree, improving the improvement of fusion degree The performance and production efficiency of the regenerated mixture.

CN119296678APending Publication Date: 2025-01-10TONGJI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411440607.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art is difficult to accurately and quickly measure the degree of fusion between new and old asphalt in the factory mixed heat regenerated asphalt mixture, resulting in design errors and affecting the performance of the mixture. Common methods are complex and time-consuming to operate, and the use of chemical reagents affects the true status of the sample.

Method used

The nanoscale modulus of new and old asphalt was tested by atomic force microscope, and the degree of fusion between new and old asphalt was predicted by nonlinear regression analysis based on the forming time of the regenerated asphalt mixture, the doping rate of old asphalt and the preheating temperature.

Benefits of technology

A simple and fast prediction of the degree of fusion between old and new bitumen is achieved, which reduces the experimental cost and time, reduces the impact on the state of the mixture, and improves the performance and production efficiency of the regenerated mixture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119296678A_ABST
    Figure CN119296678A_ABST
Patent Text Reader

Abstract

The invention discloses a method and device for predicting the fusion degree of new asphalt and old asphalt in a plant-mixed hot recycled asphalt mixture, and relates to the technical field of road engineering. According to the method, the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt in the recycled asphalt mixture are tested through the AFM technology; according to the method, the nanoscale modulus of new asphalt and the nanoscale modulus of old asphalt are considered; the new and old asphalt fusion degree can be predicted by a prediction model established by using the recycled asphalt mixture, the standing time of the formed recycled asphalt mixture, the blending rate of the waste asphalt mixture in the recycled asphalt mixture and the preheating temperature of the waste asphalt mixture when the recycled asphalt mixture is prepared, and chemical analysis, mechanical property testing and the like are not needed. The new and old asphalt fusion degree can be simply and quickly predicted, and the real fusion state of the mixture is not influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of road engineering, and in particular to a method and device for predicting the degree of fusion of new and old asphalt in a factory-mixed hot recycled asphalt mixture. Background Art

[0002] In recent years, the recycling technology of waste asphalt mixture has been increasingly used in road construction as an important means to achieve energy conservation and emission reduction in transportation construction. According to the different treatment temperatures of waste asphalt mixture, the recycling technology can be divided into hot recycling, warm recycling and cold recycling technology. In the hot recycling technology, according to the different waste material treatment sites, it can be divided into plant-mixed hot recycling technology and on-site hot recycling technology. With the advantages of stable mixture performance, small equipment investment and wide application range, plant-mixed hot recycling technology is widely used.

[0003] For factory-mixed hot recycled asphalt mixtures, the degree of fusion of new and old asphalt in the mixture will affect its design process. If the degree of fusion of new and old asphalt in the mixture is not considered when designing the recycled mixture, and the recycled mixture is designed based on the assumption of complete fusion, the designed recycled mixture will have insufficient binder, resulting in the performance of the recycled mixture failing to meet expectations.

[0004] In order to quantify the degree of fusion of new and old asphalt in recycled mixtures, researchers have proposed many methods by combining various means. These methods include chemical analysis, mechanical properties testing, etc. However, these methods are not only cumbersome to operate, but the chemical reagents used in the test process will also affect the actual degree of fusion of new and old asphalt in the mixture, resulting in errors and deviations, making it difficult to accurately reflect the actual situation. In addition, these methods usually require professional equipment and laboratory conditions, and the operation steps are complicated and time-consuming, which increases the cost and time of the experiment. This complexity and the impact of chemical reagents on samples have limited the application of these methods in actual engineering and made it difficult to promote them widely. Therefore, how to develop a simple, fast test method that has little impact on the actual state of the mixture has become an urgent problem to be solved in order to promote the effective application and promotion of recycled asphalt mixtures in engineering. Summary of the invention

[0005] The purpose of this application is to provide a method and device for predicting the degree of fusion of new and old asphalt in factory-mixed hot-recycled asphalt mixture, which can realize a simple and fast prediction of the degree of fusion of new and old asphalt without affecting the actual state of the mixture.

[0006] To achieve the above objectives, this application provides the following solutions:

[0007] In a first aspect, the present application provides a method for predicting the degree of fusion of new and old asphalt in a plant-mixed hot recycled asphalt mixture, wherein the recycled asphalt mixture includes new asphalt and old asphalt, wherein the new asphalt is newly added asphalt, and the old asphalt is asphalt in the waste asphalt mixture, and the method for predicting the degree of fusion of new and old asphalt in the plant-mixed hot recycled asphalt mixture includes:

[0008] Testing the nanoscale modulus of new asphalt;

[0009] Testing the nanoscale modulus of old asphalt;

[0010] The degree of fusion between new and old asphalt is predicted based on the placement time of the recycled asphalt mixture after molding, the blending ratio of the waste asphalt mixture in the recycled asphalt mixture, the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture, the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt.

[0011] Optionally, the nanoscale modulus of the new asphalt is tested, specifically comprising:

[0012] Use a mixing pot to mix the new asphalt and aggregate at 165°C to form;

[0013] The mixture of the formed new asphalt and aggregate was stored at -30°C for 1 day;

[0014] Cutting the frozen mixture of new asphalt and aggregate into first rectangular test blocks;

[0015] Using an atomic force microscope to collect a nanoscale modulus image of asphalt in a free asphalt region in the first rectangular parallelepiped test block as a first nanoscale modulus image;

[0016] The first nanoscale modulus image was analyzed using Nanoscope analysis software to obtain the nanoscale modulus of the new asphalt.

[0017] Optionally, the nanoscale modulus of the old asphalt is tested, including:

[0018] The waste asphalt mixture is mixed and formed at 150°C using a mixing pot;

[0019] The formed waste asphalt mixture was stored at -30°C for 1 day;

[0020] Cutting the frozen waste asphalt mixture into a second rectangular test block;

[0021] Using an atomic force microscope to collect a nanoscale modulus image of asphalt in a free asphalt region in the second cuboid test block as a second nanoscale modulus image;

[0022] The second nanoscale modulus image was analyzed using Nanoscope analysis software to obtain the nanoscale modulus of the old asphalt.

[0023] Optionally, the degree of fusion between new and old asphalt is predicted based on the placement time of the recycled asphalt mixture after molding, the blending ratio of the waste asphalt mixture in the recycled asphalt mixture, the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture, the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt, specifically including:

[0024] According to the placement time of the recycled asphalt mixture after molding, the blending ratio of the waste asphalt mixture in the recycled asphalt mixture, the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture, the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt, a fusion degree prediction model is used to predict the fusion degree of new and old asphalt.

[0025] Optionally, the fusion degree prediction model is obtained by performing nonlinear regression analysis and fitting on measured data of recycled asphalt mixture under different working conditions.

[0026] Optionally, the fusion degree prediction model is:

[0027]

[0028] Among them, DOB is the degree of fusion of new and old asphalt, E1 and E2 are the nanoscale moduli of new asphalt and old asphalt in the recycled asphalt mixture, respectively, d is the placement time of the recycled asphalt mixture after molding, R is the blending ratio of waste asphalt mixture in the recycled asphalt mixture, and T is the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture.

[0029] Optionally, the placement time of the recycled asphalt mixture after molding ranges from 3 to 30 days.

[0030] Optionally, the blending ratio R of the waste asphalt mixture in the recycled asphalt mixture ranges from 20% to 80%.

[0031] Optionally, when preparing the recycled asphalt mixture, the preheating temperature of the waste asphalt mixture ranges from 90°C to 170°C.

[0032] In a second aspect, the present application provides a device for predicting the degree of fusion of new and old asphalt in a factory-mixed hot-regenerated asphalt mixture, and the device for predicting the degree of fusion of new and old asphalt in a factory-mixed hot-regenerated asphalt mixture is used to implement the above-mentioned method for predicting the degree of fusion of new and old asphalt in a factory-mixed hot-regenerated asphalt mixture, and the device for predicting the degree of fusion of new and old asphalt in a factory-mixed hot-regenerated asphalt mixture comprises:

[0033] The first test module is used to test the nanoscale modulus of new asphalt;

[0034] The second test module is used to test the nanoscale modulus of old asphalt;

[0035] The prediction module is used to predict the degree of fusion between new and old asphalt according to the placement time of the recycled asphalt mixture after molding, the blending ratio of the waste asphalt mixture in the recycled asphalt mixture, the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture, the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt.

[0036] According to the specific embodiments provided in this application, this application discloses the following technical effects:

[0037] The present application provides a method and device for predicting the degree of fusion of new and old asphalt in a factory-mixed hot-regenerated asphalt mixture. The method uses AFM (Atomic Force Microscope) technology to test the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt in the regenerated asphalt mixture. A prediction model is established based on the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt, as well as the placement time of the regenerated asphalt mixture after molding, the blending ratio of the waste asphalt mixture in the regenerated asphalt mixture, and the preheating temperature of the waste asphalt mixture when preparing the regenerated asphalt mixture. The degree of fusion of the new and old asphalt can be predicted without the need for chemical analysis, mechanical property testing, etc., and a simple and rapid prediction of the degree of fusion of the new and old asphalt can be achieved without affecting the actual fusion state of the mixture. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 A flow chart of a method for predicting the degree of fusion of new and old asphalt in a factory-mixed hot recycled asphalt mixture provided in one embodiment of the present application;

[0040] Figure 2 A gradation curve of a recycled asphalt mixture provided in one embodiment of the present application. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0042] In order to make the above-mentioned objects, features and advantages of the present application more obvious and easy to understand, the present application is further described in detail below with reference to the accompanying drawings and specific implementation methods.

[0043] In an exemplary embodiment, Figure 1 As shown, a method for predicting the degree of fusion of new and old asphalt in a factory-mixed hot recycled asphalt mixture is provided, wherein the recycled asphalt mixture includes new asphalt and old asphalt, the new asphalt is newly added asphalt, and the old asphalt is asphalt in the waste asphalt mixture, and the method for predicting the degree of fusion of new and old asphalt in the factory-mixed hot recycled asphalt mixture includes the following steps 101 to 103. Among them:

[0044] Step 101, testing the nanoscale modulus of new asphalt.

[0045] Step 102, testing the nanoscale modulus of the old asphalt.

[0046] Step 103, predicting the degree of fusion between new and old asphalt according to the standing time of the recycled asphalt mixture after molding, the blending ratio of the waste asphalt mixture in the recycled asphalt mixture, the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture, the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt.

[0047] By implementing the above steps 101 to 103, it is possible to quickly and accurately predict the degree of fusion of new and old asphalt in the recycled mixture under different working conditions, improve the production process of the recycled mixture, and enhance the performance of the recycled mixture.

[0048] Among them, the nanoscale modulus index is quantified with the help of the Analysis module in the Nanoscope analysis software.

[0049] In another exemplary embodiment, step 103 specifically includes: predicting the degree of fusion between new and old asphalt using a fusion degree prediction model based on the placement time of the recycled asphalt mixture after molding, the blending ratio of the waste asphalt mixture in the recycled asphalt mixture, the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture, the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt.

[0050] Among them, the fusion degree prediction model is obtained by performing nonlinear regression analysis and fitting on the measured data of recycled asphalt mixture under different working conditions. The measured data are shown in Table 1.

[0051] Table 1 Orthogonal test parameters and test results of the fusion degree of new and old asphalt

[0052]

[0053]

[0054] The fusion degree prediction model obtained based on the above experiments is:

[0055]

[0056] Among them, DOB is the degree of fusion of new and old asphalt, E1 and E2 are the nanoscale moduli of new asphalt and old asphalt in the recycled asphalt mixture, respectively, d is the placement time of the recycled asphalt mixture after molding, R is the blending ratio of waste asphalt mixture in the recycled asphalt mixture, and T is the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture.

[0057] In order to further illustrate the implementation and effect of the method for predicting the degree of fusion of new and old asphalt in the factory-mixed hot-recycled asphalt mixture in the embodiment of the present application, the present application also provides the following Examples 1-3.

[0058] Example 1

[0059] SK-70 base asphalt (new asphalt), new aggregates such as limestone and basalt, and on-site milling recycled waste asphalt mixture (RAP-1) are used to prepare recycled asphalt mixture. The target gradation is 20%. The gradation curve is as follows: Figure 2 As shown. During the molding process of the recycled mixture, the preheating temperature of the waste asphalt mixture is 120℃, the preheating time is 2h, the mixing temperature of the recycled mixture is 165℃, the heating temperature of the new asphalt is 165℃, and the asphalt, aggregate and mineral powder are mixed in three steps. First, the waste asphalt mixture and the new aggregate are mixed, then the new asphalt is added for mixing, and finally the mineral powder is added. The mixing time of each step is 90s, and the total mixing time is 270s. After molding, the recycled mixture is left at room temperature (25℃) for 10 days.

[0060] Step 1: Test the nanoscale modulus E1 of the new asphalt used in the recycled mixture.

[0061] ① Use a mixing pot to mix SK-70 matrix asphalt with limestone and basalt aggregate at 165°C.

[0062] ②Store the formed asphalt mixture at -30℃ for 1 day.

[0063] ③Cut the frozen asphalt mixture into 30mm*30mm*20mm rectangular test blocks, namely the first rectangular test blocks.

[0064] ④ Using atomic force microscopy technology to collect a nanoscale modulus image of the asphalt in the free asphalt area of ​​the first rectangular specimen, that is, the first nanoscale modulus image.

[0065] ⑤ Use Nanoscope analysis software to analyze the first nanoscale modulus image and obtain the nanoscale modulus of the new asphalt E1 = 343 MPa.

[0066] Step 2: Test the nanoscale modulus E2 of asphalt in waste asphalt mixture.

[0067] ① Use a mixing pot to mix and shape the RAP-1 old material at 165℃.

[0068] ②Store the formed asphalt mixture at -30℃ for 1 day.

[0069] ③Cut the frozen asphalt mixture into 30mm*30mm*20mm rectangular test blocks, i.e. the second rectangular test blocks.

[0070] ④ Use atomic force microscopy technology to collect the nanoscale modulus image of the asphalt in the free asphalt area in the second rectangular specimen, that is, the second nanoscale modulus image.

[0071] ⑤ The second nanoscale modulus image was analyzed using Nanoscope analysis software to obtain the nanoscale modulus of the old asphalt E2 = 891 MPa.

[0072] Step 3: Record the placement time d = 10 days after the recycled mixture is formed.

[0073] Step 4: Record the blending ratio of waste asphalt mixture in the recycled mixture (R = 20%).

[0074] Step 5: Record the preheating temperature T = 120°C of the waste asphalt mixture used to prepare the recycled mixture.

[0075] Step 6: According to the nanoscale modulus of the new and old asphalt in the mixture, the placement time after molding, the blending rate of the waste asphalt mixture and the preheating temperature of the waste asphalt mixture, they are compared with the actual values. The comparison results are shown in Table 2.

[0076] Table 2 Deviation between predicted values ​​and measured values

[0077] Working condition number Actual value (%) Predicted value (%) error(%) 1 82.4 74.7 9.3

[0078] Example 2

[0079] The recycled asphalt mixture was prepared by using No. 90 base asphalt, new aggregates of limestone and basalt, and waste asphalt mixture (RAP-2). The target gradation was 20%. The gradation curve is as follows: Figure 2As shown. During the molding process of the recycled mixture, the preheating temperature of the waste asphalt mixture is 150℃, the preheating time is 2h, the mixing temperature of the recycled mixture is 165℃, the heating temperature of the new asphalt is 165℃, and the asphalt, aggregate and mineral powder are mixed in three steps. First, the waste asphalt mixture and the new aggregate are mixed, then the new asphalt is added for mixing, and finally the mineral powder is added. The mixing time of each step is 90s, and the total mixing time is 270s. After molding, the recycled mixture is left at room temperature (25℃) for 14 days.

[0080] Step 1: Test the nanoscale modulus E1 of the new asphalt used in the recycled mixture.

[0081] ① Use a mixing pot to mix No. 90 base asphalt with limestone and basalt aggregate at 165°C to form.

[0082] ②Store the formed asphalt mixture at -30℃ for 1 day.

[0083] ③Cut the frozen asphalt mixture into 30mm*30mm*20mm rectangular test blocks, namely the first rectangular test blocks.

[0084] ④ Using atomic force microscopy technology to collect a nanoscale modulus image of the asphalt in the free asphalt area of ​​the first rectangular specimen, that is, the first nanoscale modulus image.

[0085] ⑤ Use Nanoscope analysis software to analyze the first nanoscale modulus image and obtain the nanoscale modulus of the new asphalt E1 = 279 MPa.

[0086] Step 2: Test the nanoscale modulus E2 of asphalt in waste asphalt mixture.

[0087] ① Use a mixing pot to mix and shape the RAP-2 old material at 165℃.

[0088] ②Store the formed asphalt mixture at -30℃ for 1 day.

[0089] ③Cut the frozen asphalt mixture into 30mm*30mm*20mm rectangular test blocks, i.e. the second rectangular test blocks.

[0090] ④ Use atomic force microscopy technology to collect the nanoscale modulus image of the asphalt in the free asphalt area in the second rectangular specimen, that is, the second nanoscale modulus image.

[0091] ⑤ The second nanoscale modulus image was analyzed using Nanoscope analysis software to obtain the nanoscale modulus of the old asphalt E2 = 769 MPa.

[0092] Step 3: Record the placement time of the recycled mixture after molding (d = 14 days).

[0093] Step 4: Record the blending ratio of waste asphalt mixture in the recycled mixture (R = 20%).

[0094] Step 5: Record the preheating temperature T = 150°C of the waste asphalt mixture used to prepare the recycled mixture.

[0095] Step 6: According to the nanoscale modulus of the new and old asphalt in the mixture, the placement time after molding, the blending rate of the waste asphalt mixture and the preheating temperature of the waste asphalt mixture, they are compared with the actual values. The comparison results are shown in Table 3.

[0096] Table 3 Deviation between predicted values ​​and measured values

[0097] Working condition number Actual value (%) Predicted value (%) error(%) 1 96.2 85.3 11.3

[0098] Example 3

[0099] The recycled asphalt mixture was prepared by using No. 70 base asphalt, new aggregates of limestone and basalt, and waste asphalt mixture (RAP-3). The target gradation was 30%. The gradation curve is as follows: Figure 2 As shown. During the molding process of the recycled mixture, the preheating temperature of the waste asphalt mixture is 90℃, the preheating time is 2h, the mixing temperature of the recycled mixture is 165℃, the heating temperature of the new asphalt is 165℃, and the asphalt, aggregate and mineral powder are mixed in three steps. First, the waste asphalt mixture and the new aggregate are mixed, then the new asphalt is added for mixing, and finally the mineral powder is added. The mixing time of each step is 90s, and the total mixing time is 270s. After molding, the recycled mixture is left at room temperature (25℃) for 10 days.

[0100] Step 1: Test the nanoscale modulus E1 of the new asphalt used in the recycled mixture.

[0101] ① Use a mixing pot to mix No. 90 base asphalt with limestone and basalt aggregate at 165°C to form.

[0102] ②Store the formed asphalt mixture at -30℃ for 1 day.

[0103] ③Cut the frozen asphalt mixture into 30mm*30mm*20mm rectangular test blocks, namely the first rectangular test blocks.

[0104] ④ Using atomic force microscopy technology to collect a nanoscale modulus image of the asphalt in the free asphalt area of ​​the first rectangular specimen, that is, the first nanoscale modulus image.

[0105] ⑤ Use Nanoscope analysis software to analyze the first nanoscale modulus image and obtain the nanoscale modulus of the new asphalt E1 = 343 MPa.

[0106] Step 2: Test the nanoscale modulus E2 of asphalt in waste asphalt mixture.

[0107] ① Use a mixing pot to mix and shape the RAP-3 old material at 165℃.

[0108] ②Store the formed asphalt mixture at -30℃ for 1 day.

[0109] ③Cut the frozen asphalt mixture into 30mm*30mm*20mm rectangular test blocks, i.e. the second rectangular test blocks.

[0110] ④ Use atomic force microscopy technology to collect the nanoscale modulus image of the asphalt in the free asphalt area in the second rectangular specimen, that is, the second nanoscale modulus image.

[0111] ⑤ The second nanoscale modulus image was analyzed using Nanoscope analysis software to obtain the nanoscale modulus of the old asphalt E2 = 864 MPa.

[0112] Step 3: Record the placement time d = 10 days after the recycled mixture is formed.

[0113] Step 4: Record the blending ratio of waste asphalt mixture in the recycled mixture (R = 30%).

[0114] Step 5: Record the preheating temperature T = 90°C of the waste asphalt mixture used to prepare the recycled mixture.

[0115] Step 6: According to the nanoscale modulus of the new and old asphalt in the mixture, the placement time after molding, the blending rate of the waste asphalt mixture and the preheating temperature of the waste asphalt mixture, they are compared with the actual values. The comparison results are shown in Table 4.

[0116] Table 4 Deviation between predicted values ​​and measured values

[0117] Working condition number Actual value (%) Predicted value (%) error(%) 1 87.9 79.5 9.5

[0118] It is not difficult to see from Tables 2 to 4 that the method provided in the present application can quickly and accurately predict the degree of fusion of new and old asphalt in recycled mixtures under different working conditions, and the prediction error can be controlled within 15%. If the error between the predicted value and the actual detection value of the recycled mixture exceeds 20%, it is generally regarded as a prediction failure.

[0119] Based on the same inventive concept, the embodiment of the present application also provides a device for realizing the prediction of the degree of fusion of new and old asphalt in the plant-mixed hot regenerated asphalt mixture involved above. The implementation scheme for solving the problem provided by the device is similar to the implementation scheme recorded in the above method, so the specific limitations in the embodiments of one or more devices for predicting the degree of fusion of new and old asphalt in the plant-mixed hot regenerated asphalt mixture provided below can refer to the limitations of the method for predicting the degree of fusion of new and old asphalt in the plant-mixed hot regenerated asphalt mixture above, and will not be repeated here.

[0120] In an exemplary embodiment, a device for predicting the degree of fusion of new and old asphalt in a factory-mixed hot recycled asphalt mixture is provided, comprising:

[0121] The first test module is used to test the nanoscale modulus of new asphalt.

[0122] The second test module is used to test the nanoscale modulus of old asphalt.

[0123] The prediction module is used to predict the degree of fusion between new and old asphalt according to the placement time of the recycled asphalt mixture after molding, the blending ratio of the waste asphalt mixture in the recycled asphalt mixture, the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture, the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt.

[0124] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0125] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and core ideas of this application. At the same time, for those skilled in the art, according to the ideas of this application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting this application.

Claims

1. A method for predicting the degree of fusion of new and old asphalt in factory-mixed hot recycled asphalt mixture, characterized in that: The recycled asphalt mixture includes new asphalt and old asphalt, wherein the new asphalt is newly added asphalt, and the old asphalt is asphalt in the waste asphalt mixture. The method for predicting the degree of fusion of new and old asphalt in the factory-mixed hot recycled asphalt mixture includes: Testing the nanoscale modulus of new asphalt; Testing the nanoscale modulus of old asphalt; The degree of fusion between new and old asphalt is predicted based on the placement time of the recycled asphalt mixture after molding, the blending ratio of the waste asphalt mixture in the recycled asphalt mixture, the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture, the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt.

2. The method for predicting the degree of fusion of new and old asphalt in factory-mixed hot recycled asphalt mixture according to claim 1, characterized in that: The nanoscale modulus of the new asphalt is tested, specifically comprising: Use a mixing pot to mix the new asphalt and aggregate at 165°C to form; The mixture of new asphalt and aggregate after forming is stored at -30°C for 1 day; Cutting the frozen mixture of new asphalt and aggregate into first rectangular test blocks; Using an atomic force microscope to collect a nanoscale modulus image of asphalt in a free asphalt region in the first rectangular parallelepiped test block as a first nanoscale modulus image; The first nanoscale modulus image was analyzed using Nanoscope analysis software to obtain the nanoscale modulus of the new asphalt.

3. The method for predicting the degree of fusion of new and old asphalt in factory-mixed hot recycled asphalt mixture according to claim 1, characterized in that: Testing the nanoscale modulus of old asphalt, including: The waste asphalt mixture is mixed and formed at 150°C using a mixing pot; The formed waste asphalt mixture was stored at -30°C for 1 day; Cutting the frozen waste asphalt mixture into a second rectangular test block; Using an atomic force microscope to collect a nanoscale modulus image of asphalt in a free asphalt region in the second cuboid test block as a second nanoscale modulus image; The second nanoscale modulus image was analyzed using Nanoscope analysis software to obtain the nanoscale modulus of the old asphalt.

4. The method for predicting the degree of fusion of new and old asphalt in factory-mixed hot recycled asphalt mixture according to claim 1, characterized in that: According to the placement time of the recycled asphalt mixture after molding, the blending ratio of the waste asphalt mixture in the recycled asphalt mixture, the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture, the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt, the degree of fusion of the new and old asphalt is predicted, including: According to the placement time of the recycled asphalt mixture after molding, the blending ratio of the waste asphalt mixture in the recycled asphalt mixture, the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture, the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt, a fusion degree prediction model is used to predict the fusion degree of new and old asphalt.

5. The method for predicting the degree of fusion of new and old asphalt in factory-mixed hot recycled asphalt mixture according to claim 4, characterized in that: The fusion degree prediction model is obtained by performing nonlinear regression analysis and fitting on measured data of recycled asphalt mixture under different working conditions.

6. The method for predicting the degree of fusion of new and old asphalt in factory-mixed hot recycled asphalt mixture according to claim 4 or 5, characterized in that: The fusion degree prediction model is: Among them, DOB is the degree of fusion of new and old asphalt, E1 and E2 are the nanoscale moduli of new asphalt and old asphalt in the recycled asphalt mixture, respectively, d is the placement time of the recycled asphalt mixture after molding, R is the blending ratio of waste asphalt mixture in the recycled asphalt mixture, and T is the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture.

7. The method for predicting the degree of fusion of new and old asphalt in factory-mixed hot recycled asphalt mixture according to claim 1, characterized in that: The placement time of recycled asphalt mixture after molding ranges from 3 days to 30 days.

8. The method for predicting the degree of fusion of new and old asphalt in factory-mixed hot recycled asphalt mixture according to claim 1, characterized in that: The blending ratio of waste asphalt mixture in recycled asphalt mixture ranges from 20% to 80%.

9. The method for predicting the degree of fusion of new and old asphalt in factory-mixed hot recycled asphalt mixture according to claim 1, characterized in that: When preparing recycled asphalt mixture, the preheating temperature of the waste asphalt mixture ranges from 90°C to 170°C.

10. A device for predicting the degree of fusion of new and old asphalt in factory-mixed hot recycled asphalt mixture, characterized in that: The device for predicting the degree of fusion of new and old asphalt in a factory-mixed hot-regenerated asphalt mixture is used to implement the method for predicting the degree of fusion of new and old asphalt in a factory-mixed hot-regenerated asphalt mixture according to any one of claims 1 to 9, and the device for predicting the degree of fusion of new and old asphalt in a factory-mixed hot-regenerated asphalt mixture comprises: The first test module is used to test the nanoscale modulus of new asphalt; The second test module is used to test the nanoscale modulus of old asphalt; The prediction module is used to predict the degree of fusion between new and old asphalt according to the placement time of the recycled asphalt mixture after molding, the blending ratio of the waste asphalt mixture in the recycled asphalt mixture, the preheating temperature of the waste asphalt mixture when preparing the recycled asphalt mixture, the nanoscale modulus of the new asphalt and the nanoscale modulus of the old asphalt.